EFFECT OF ADDITIONAL CARRAGENAN ON THE QUALITY OF GRILLED CATFISH (Pangasius hypopthalmus) CAKE - Danny Handoko; N. Ira Sari; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aimed to determine the effect of the addition of carrageenan on the quality of grilled catfish cake by looking at the value of organoleptic, folding test, and proximate value. The method used is the experimental method with a Completely Randomized Design (CRD) consisting of 4 levels of treatment ie 0% carrageenan (K0), 2.5% carrageenan (K1), 5% carrageenan (K2) and 7.5 % carrageenan (K3). The tested parameters were organoleptic (appearance, taste, texture and flavor), folding test and the proximate analysis (moisture, protein, fa, asht content and crude fiber). The results showed that the addition of carrageenan 5% is the best treatment for organoleptic test, folding test and chemical test, with appearance 6.68 (grilled catfish cake is homogen and tight), taste 5.53 (typical taste of grilled catfish cake neither taste of carrageenan), texture 7,03 (grilled catfish cake is chewy), flavor 5,32 (flavor of grilled catfish cake more dominant than carrageenan), folding test4.66 (not crack if folded), with moisture content 43.14%, protein content 9.62%, fat content 1.01%, ash content 1.01% and crude fiber1,33%. Keywords:Grilled catfish cake, carrageenan, organoleptic, proximate